(untitled) (International Journal of Engineering and Computer Science, 2014)
Image quality assessment means estimating the quality of an image and it is used for many image processing applications. Image quality can be measured in two ways, subjective and objective method. In this paper, I am focusing on the FR objective image quality metric, where the quality of the distorted test images are obtained based on the comparison with the reference image which is assumed to be perfect in quality. In this we evaluate the MSSIM IQA metric for colour image at different noise density level .